PAINBRUSH AND STYLUS OF VASYL MASIUTYN - Мочернюк, Н. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the investigation of the literary works of the Ukrainian artist Vasyl Masiutyn (1884-1955). The plot and compositional, genre and idea aspects of the stories «Two from one» (1936) and “Princess Nefreta” (1938) have been examined in the paper. The author pays attention to the literary and fine arts interrelation in the artist’s biography. The analysis of Vasyl Masiutyn’s prose helps to expose the development peculiarities of the national culture. The study presented is the part of the research of the universalistic artists’ creative work in the period between the world wars in the Ukrainian literature.